Understanding Foreign Language Anxiety: A Case Study of German Learners at SMA Negeri 3 Yogyakarta - Evita Aulia Nur Rohmah; Iman Santoso (Universitas Negeri Makassar, 2026)
Abstract. In the era of globalization, mastering foreign languages is crucial, especially German, is very important. However, learning German in Indonesia often faces significant challenges due to complex grammar and pronunciation, which can trigger anxiety about learning foreign languages among students. This study aims to analyze the forms and causes of learning anxiety experienced by students at SMA Negeri 3 Yogyakarta, a PASCH school partnered with the Goethe-Institut. This study uses a qualitative case study design. Data were collected through questionnaires, interviews, and observations, with validity ensured through the use of triangulation techniques. The analysis was conducted using Miles and Huberman's interactive model, which consists of data collection, reduction, presentation, and conclusion drawing. The findings show that internal and external factors contribute to learning anxiety. Internally, 45% of students reported limited vocabulary, 40% were afraid of grammatical errors, and 56% experienced difficulties with confidence and pronunciation when speaking. Externally, the dominant forms of anxiety were speaking anxiety, test anxiety, and listening anxiety, which often inhibited spontaneous communication and active participation in class. These findings highlight the forms of anxiety students experience when learning German. More broadly, this study contributes to the understanding of foreign language anxiety in the context of multilingual education and provides insights for improving foreign language teaching practices globally, particularly in non-native language learning environments. Keywords: Learning anxiety, foreign language, German language, Pasch-Schule